Protectionism vs Liberalization Policies in World Shipping Industry - Λέκκας, Νικόλαος (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Ναυπηγών Μηχανολόγων Μηχανικών, 2017)
This specific study focused on the characteristics of different system policies applied on the maritime market, the advantages and disadvantages and how they shape the world trading system. In recent years, the domestic transportations have become a major issue of political value. The legislation about the short sea shipping industry affects the shipping companies in order to protect the domestic companies from the uneven competition with global colossal companies keeping them intact while helping the economy at the same time by exporting goods and improving the shipping lines. For these specific reasons in order to protect the good of the shipping industry: a) the protectionism policies and b) the liberalization policies in maritime industry. The protectionism policies through different means (tariffs, quotas, non-tariff barriers etc.) aim to reduce the number of imports coming into a country. In this way, there is noticeable growth of the domestic shipping industry, new job opportunities, protection of infant shipping industries etc. Although it is natural that disadvantages occur along the way as the shipping companies are restricted by the laws, free market cannot be fully developed under those circumstances. Also the monopoly owned by the domestic companies concerning the shipping fare is still. The liberalized policies in maritime are applied more and more through the years especially in developed countries as they promote a global network of product exchange. Although the liberalized system policies face difficulties as it quite complicated to achieve agreements between global scale companies of different class in order to operate under a common legal framework It is reasonable that these two different systems of policies that are applied conflict with one another because of contradictions stemming from the basic ideas on which supported each one. Despite the fact that the liberalized market policies represent a whole and intangible system it is not wise to ignore the advantages. The free market system requires the development of liberalization policies in order to create an international trading network and the improvement of the global.